2022
DOI: 10.3847/1538-4357/ac930d
|View full text |Cite
|
Sign up to set email alerts
|

Solar-cycle-related Variation of Differential Rotation of the Chromosphere

Abstract: Solar-cycle-related variation of the solar chromospheric rotation is studied by analyzing the chromospheric rotation rate of 938 synoptic maps generated from the Ca ii K line at the Mount Wilson Observatory during the period of 1915 August 10 to 1985 July 7. The results obtained are as follows: (1) The parameters A (the equatorial rotation rate) and B (the latitudinal gradient of rotation) in the standard form of differential rotation both show a decreasing trend in the considered time frame, although A has we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
2
3
0
Order By: Relevance
“…In addition, we discussed the correlation between the rotation rate and the solar activity represented by the yearly mean total sunspot numbers, and found the rotation rate of the STR follows the overall trend as solar activity, which supports the results reported by Japaridze & Chargeishvili (2016), Sharma et al (2021), Wan & Gao (2022), and Wan & Li (2022). In the comparison of the rotational coefficients, we found the STR rotates more slowly and more rigidly than the solar chromosphere and the corona.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In addition, we discussed the correlation between the rotation rate and the solar activity represented by the yearly mean total sunspot numbers, and found the rotation rate of the STR follows the overall trend as solar activity, which supports the results reported by Japaridze & Chargeishvili (2016), Sharma et al (2021), Wan & Gao (2022), and Wan & Li (2022). In the comparison of the rotational coefficients, we found the STR rotates more slowly and more rigidly than the solar chromosphere and the corona.…”
Section: Discussionsupporting
confidence: 87%
“…These behaviors suggest that the rotation rate of the STR follows the same trend as solar activity and is modulated by the solar cycle as well. Some authors have reported the Sun rotates faster during the solar cycle maxima by analyzing different data sets (Japaridze & Chargeishvili 2016;Sharma et al 2021;Wan & Gao 2022;Wan & Li 2022), and our finding is in agreement with their results. Especially for the result of Sharma et al (2021), who studied the rotation of the STR as well.…”
Section: Cycle-related Variations Of the Rotation Rate And Solar Acti...supporting
confidence: 93%
See 3 more Smart Citations